THE EFFECT OF FINANCING TO DEPOSIT RATIO (FDR) AND THE MONEY SUPPLY ON PROFITABILITAS IN SHARIA BUSINESS UNIT FOR THE 2016-2020 PERIOD - Mutiah Khaira Sihotang (IQTISHADUNA, 2021)
This study aims to determine the effect of FDR and the money supply on profitability as proxied by Return On Assets (ROA), a study on Sharia Business Units for the 2016-2020 period. The sample selection in this study used purposive sampling method. The population in this study is the financial statements of Sharia Business Units in Indonesia and the sample in this study is the monthly financial statements of Sharia Business Units in Indonesia for 2016-2020. The data in this study will be processed using SPSS software with multiple regression. The results of this study state that partially the independent variables in this study are Financing to Deposit Ratio (FDR) and the money supply has a significant effect on Return On Assets (ROA) of Islamic Business Units in Indonesia with a significance level of 0.000. Then, simultaneously Financing to Deposit Ratio (FDR) and the money supply have a significant effect on the Return On Assets (ROA) of Sharia Business Units in Indonesia with a significance level of 0.000 and an fhitung value of 50,742.